FINANCIAL PERFORMANCE ANALYSIS USING PROFITABILITY RATIO AT PT. INDOFOOD MAKMUR TBK SUCCESS. REGISTERED ON THE INDONESIAN STOCK EXCHANGE (BEI) 2021-2022 - Irada Sinta; Lusi Afriliana; Riska Yanti; Zulfa Riza; Rico Nur Ilham (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Financial performance is a description of the achievements that management has achieved in carrying out its function of managing company assets each period. Financial performance is needed to measure the success of cooperatives in achieving their goals, namely increasing the welfare of members and the ability to pay debts. The financial performance of a cooperative is a reflection of the progress of the cooperative. Financial performance is usually reflected in financial reports, so that financial reports are a picture of a company at a certain time, usually arranged in periods or accounting cycles which show the financial condition that a company has achieved in a certain period.